An Integrated Model of Motivation, Workload, Subjective Norms, and Skills Predicting Triage Accuracy Among Emergency Nurses - Novita Ana Anggraini; Beres Sehat Tua Naibaho; Rahmania Ambarika; Sri Haryuni (Care : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Accurate triage is fundamental to emergency nursing because it determines patient prioritization and influences clinical outcomes. Although previous studies have identified motivation, workload, subjective norms, and clinical competence as factors associated with triage performance, these determinants have largely been investigated independently. Evidence regarding their combined influence on triage accuracy remains limited. This study aimed to develop and evaluate an integrated model examining the effects of work motivation, workload, subjective norms, and clinical competence on triage accuracy among emergency nurses. A cross-sectional analytic study was conducted among 101 emergency nurses from three hospitals in Karo District, Indonesia. Participants were selected using stratified sampling. Data were collected using validated questionnaires to measure work motivation, workload, and subjective norms, while clinical competence and triage accuracy were assessed through structured observation. Multiple linear regression analysis was performed using SPSS to determine the relative contribution of each predictor to triage accuracy. The integrated regression model significantly explained 76.3% of the variance in triage accuracy (R² = 0.763; F = 34.395; p = 0.003). Work motivation (B = 0.619; p 0.001), workload (B = 0.455; p = 0.022), subjective norms (B = 0.776; p = 0.015), and clinical competence (B = 0.256; p 0.001) were all significant predictors of triage accuracy. Overall, nurses with higher motivation, stronger subjective norms, and better clinical competence demonstrated greater triage accuracy, whereas excessive workload was associated with poorer performance.Conclusion: Triage accuracy is influenced by the combined effects of behavioral, organizational, social, and competency-related factors. These findings support the implementation of integrated interventions, including competency-based training, supportive leadership, motivation enhancement, and effective workload management, to strengthen emergency nurses' triage performance and improve patient safety.